Erratum - Utine CA (Dove Medical Press, 2011)
Utine CA. Update and critical appraisal of the use of topical azithromycin ophthalmic 1% (AzaSite®) solution in the treatment of ocular infections. Clin Ophthalmol. 2011;5:801-809.Table 2 inaccurately states that Bremond-Grignac used AzaSite® in their study. The ophthalmic preparation used was in fact Azyter®. Original Article